Beyond "Just Do It" - Adam C. Landon; Michael A. Tarrant; Donald L. Rubin; Lee Stoner (SAGE Publishing, 2017)
Study abroad is believed to be a transformative learning experience for students. However, the extent to which study abroad adds value beyond what is possible on campus needs to be demonstrated. In this paper, we document the learning outcomes assessment undertaken by a faculty-led study-abroad program at a large university in the U.S. Southeast. Specifically, we describe the development of a theory-based pedagogical model of global citizenship for short-term study abroad and efforts to document student learning associated with its constructs. The results of these efforts indicate that when student learning outcomes and study-abroad pedagogy are aligned with theory, and rigorously assessed, the opportunity to demonstrate learning is possible, and opportunities for instructional improvement present themselves.